Asymmetric Brønsted acid catalysis with chiral carboxylic acids. (21st July 2017) - Min, Chang; Seidel, Daniel
Abstract : This review provides an overview of various catalytic enantioselective transformations that utilize chiral carboxylic acids as Brønsted acid catalysts. Abstract : Chiral Brønsted acids have found widespread applications as organocatalysts. Weakly acidic species such as diols and (thio)ureas, typically classified as hydrogen bonding catalysts, as well as stronger phosphoric acids, have proven to be highly effective in catalyzing a wide range of asymmetric transformations. In contrast, the use of chiral carboxylic acids as Brønsted acid catalysts is much less developed but has recently garnered increased attention. Given that their p K a 's generally lie between those of typical hydrogen bond donors and chiral phosphoric acids, chiral carboxylic acids provide the opportunity to activate a different set of substrates requiring intermediate catalyst acidity. In addition, by taking advantage of judicious catalyst design, the acidity of carboxylic acids can be modulated, for instance by stabilizing the corresponding carboxylate counterion. This review provides an overview of this field, with the aim of highlighting both catalyst design and synthetic applications.